Low Hydrophobic Mismatch Scores Calculated for HLA-A/B/DR/DQ Loci Improve Kidney Allograft Survival - Bekbolsynov, Dulat; Mierzejewska, Beata; Borucka, Jadwiga; Liwski, Robert S.; Greenshields, Anna L.; Breidenbach, Joshua; Gehring, Bradley; Leonard-Murali, Shravan; Khuder, Sadik A.; Rees, Michael; Green, Robert C.; Stepkowski, Stanislaw M. (Frontiers in Immunology, 2020)
We evaluated the impact of human leukocyte antigen (HLA) disparity (immunogenicity; IM) on long-term kidney allograft survival. The IM was quantified based on physicochemical properties of the polymorphic linear donor/recipient HLA amino acids (the Cambridge algorithm) as a hydrophobic mismatch score (HMS). High-resolution HLA-A/B/DR/DQ types were imputed to calculate HMS for primary/re-transplant recipients of deceased donor transplants. The multiple Cox regression showed the association of HMS with graft survival and other confounders. The HMS integer scale of 0 to 10 showed the most survival benefits between HMS 0 and 3. Indeed, the KaplanMeier analysis showed that the HMS=0 group had 18.1-year median graft survival, a 5-year benefit over the HMS>0 group; transplants with HMS≤3.0 had 16.7-year graft survival, a 3.8-year better than HMS>3.0 group; and, transplants with HMS≤7.8 had 14.3-year grafts survival, a 1.8-year improvement over HMS>7.8 group. Additionally, the importance of HLA-DR and -DQ HMS for graft survival was shown. Importantly, in our simulation of 1,000 random donor/recipient pairs, 75% with HMS>3.0 were re-matched into HMS≤3.0 and remaining 25% into HMS≥7.8: after rematching, the graft survival of 13.5 years would increase to 16.3 years. Thus, this clinically viable approach allows for matching donors to recipients with low/medium IM donors while preventing transplants with high IM donors.